Lucie Česálková (ed.): Staré pověsti české - Rogoff, Jana (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
Jana Rogoff’s review of a book Staré pověsti české edited by Lucie Česálková